ACADEMIC SUPERVISION IN IMPROVING TEACHERS’ SKILLS DURING THE LEARNING PROCESS AT ELEMENTARY SCHOOL - Endriani; Fefi Yulita (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
The principal has an obligation to improve the quality of teachers in the learning process at school. Observations found that many learning processes carried out by elementary school teachers were not in accordance with the characteristics of elementary school students, indicating the need for improvement. The purpose of this study was to determine the improvement of teachers’ skills in the learning process at elementary schools through academic supervision activities. This research was a classroom action research adapted from McTaggart and Kemmis's classroom action research design, consisting of stages of planning, implementation, observation, and reflection. The findings showed that there was an increase in teachers’ implementation skills in the learning process, with an average score of 68.46 in cycle I, which increased to 86.10 in cycle II. This proved that academic supervision activities effectively improved teachers’ skills in the learning process at elementary schools. The implication of this research is that it can be used as a reference for supervisors to enhance teachers’ skills in conducting the learning process.